Value-at-risk for South-East Asian stock markets: Stochastic volatility vs. GARCH - Paul Bui Quang; Tony Klein; Nguyen Nam Hai; Thomas Walther (Journal of Risk and Financial Management, 2018)
This study compares the performance of several methods to calculate the Value-at-Risk of the six main ASEAN stock markets. We use filtered historical simulations, GARCH models, and stochastic volatility models. The out-of-sample performance is analyzed by various backtesting procedures. We find that simpler models fail to produce sufficient Value-at-Risk forecasts, which appears to stem from several econometric properties of the return distributions. With stochastic volatility models, we obtain better Value-at-Risk forecasts compared to GARCH. The quality varies over forecasting horizons and across markets. This indicates that, despite a regional proximity and homogeneity of the markets, index volatilities are driven by different factors.
Keywords: C58; F37; G15; G17; 330; ASEAN; GARCH; stochastic volatility; Value-at-Risk